Surgical failure following primary retinal detachment surgery by vitrectomy: risk factors and functional outcomes. Issue 9 (13th December 2010) - Wickham, Louisa; Ho-Yen, Gregory O; Bunce, Catey; Wong, David; Charteris, David G
Abstract : Aim: To identify preoperative features associated with surgical failure following vitrectomy using data collected in a large, prospective randomised controlled trial. Outcomes of patients who redetached were then examined in more detail. Methods: 615 patients were analysed as part of an randomised controlled trial investigating the use of 5-fluorouracil and low-molecular-weight heparin. Treatment status had no effect on success rates and did not therefore form part of the analyses. Failure was defined as retinal redetachment within 6 months of primary vitrectomy. Univariate logistic regression analysis was used to assess association between failure and putative risk factors (age, pathological myopia, intraocular pressure, vitreous haemorrhage, previous lens extraction, uveitis, number of retinal quadrants detached, number and distribution of retinal breaks, and grade C proliferative vitreoretinopathy (PVR)). Additional characteristics of patients were then elucidated including number of operations required to achieve retinal reattachment, surgical techniques used and final logMAR visual acuity. Results: 96 patients (15.6%) redetached following surgery, and 37 failed due to PVR. Surgical failure was associated with number of retinal quadrants detached (OR per increase, 1.69 (1.33 to 2.15) p<0.001) and grade C PVR (OR 3.98 (1.47 to 10.73) p=0.006). Inferior breaks were not identified as a risk factor (p=0.602). Repeat retinal detachment surgery showed a trend towards reduced visual acuity at 6 months providing PVR did not develop. PVR resulted in a significant deterioration in visual acuity. Conclusions: The extent of retinal detachment and preoperative PVR are risk factors for surgical failure following vitrectomy for primary retinal detachment. PVR was again confirmed as the major factor influencing visual outcomes.